Feasibility of Modified Short-Course Radiotherapy Combined With a Chemoradiosensitizer for T3 Rectal Cancer. Issue 5 (May 2015) - Beppu, Naohito; Matsubara, Nagahide; Kakuno, Ayako; Doi, Hiroshi; Kamikonya, Norihiko; Yamanaka, Naoki; Yanagi, Hidenori; Tomita, Naohiro
Abstract : BACKGROUND: 5-Fluorouracil-based chemotherapy is considered to be a radiosensitizer; however, conventional short-course radiotherapy combined with chemotherapy is generally thought to not be feasible because of the prevalence of side effects. OBJECTIVE: The aim of this study was to evaluate the feasibility of modified short-course radiotherapy combined with a chemoradiosensitizer for T3 rectal cancer. DESIGN AND SETTINGS: This study was retrospective in nature and used a prospectively collected database. PATIENTS: Patients with T3 rectal cancer located below the peritoneum reflection were selected. INTERVENTIONS: A total dose of 25 Gy of radiotherapy was administered in 10 fractions of 2.5 Gy each for 5 days. Radiotherapy was performed with S-1 as a radiosensitizer from day 1 to day 10. Surgery was targeted to be performed 4 weeks after radiotherapy. MAIN OUTCOME MEASUREMENTS: The morbidity, sphincter-preserving rate, anal function, and long-term outcomes were assessed. RESULTS: All patients (n = 170) completed the radiotherapy regimen and 166 (97.6%) completed the combination regimen with chemotherapy. A total of 149 patients (87.6%) had sphincter-preserving surgery (double stapling technique (DST), 58 patients; intersphincteric resection (ISR), 91 patients), and postoperative complications were relatively mild (anastomotic leakage, 15.4%; intra-abdominal infection, 8.2%). Among those undergoing sphincter preserving surgery, the 5-year local relapse-free survival rate was 94.3% in the DST group, and 89.8% in the ISR group. With respect to the anal function, the Wexner score the first year after stoma closure for the double-stapling technique group was 6 and that for intersphincteric resection was 15; however, the score for the intersphincteric resection group was improved to 8 at 4 years after stoma closure. LIMITATIONS: This study had limitations because it was an uncontrolled, 1-arm, retrospective review with a small sample size. CONCLUSIONS: Modified short-course radiotherapy combined with chemoradiosensitizer is a feasible approach for treating T3 rectal cancer. With the use of the short-course approach, efforts to reduce the incidence of side effects by appropriately prolonging the waiting period enable the administration of combination treatment with short-course radiotherapy and chemotherapy.